Glutathione S-transferase CrGST24 in the differentiation of adventitious buds from Camellia reticulata callus - Cao, Zihang; Wang, Jianzhao; Gong, Yikai; Yin, Xian; Yang, Cheng; Yang, Ting; Wu, Tian (Frontiers in Plant Science, 2025)
IntroductionCamellia reticulata holds cultural and horticultural significance in traditional Chinese gardens, as a regional endemic species in Yunnan Province. However, during the in vitro regeneration process of C. reticulata, there is often a phenomenon of low efficiency of adventitious bud differentiation or no adventitious bud differentiation at all.MethodsIn previous study, we observed significant morphological differences between the callus tissues of C. reticulata ‘Zipao’ and wild species. The callus of ‘Zipao’ was white and loosely textured, the wild species was green and hard. To investigate the differences between these two types of callus, we conducted transcriptome analysis and identified a differentially expressed gene GST24, which is closely related to the synthesis of glutathione (GSH). Heterologous transformation of CrGST24 into tobacco (Nicotiana tabacum) was conducted.Results and discussionThe CrGST24 gene promoted the synthesis of endogenous auxin and cytokinin in transgenic tobacco by regulating the expression of transcription factors related to auxin and cytokinin. Exogenous IBA, 6-BA, and red-blue light treatment increased the levels of auxins and cytokinins in C. reticulata callus, thereby promoting adventitious bud differentiation. Additionally, CrGST24 interacted with CrGSHB and CrDHAR2 genes, facilitating GSH and AsA synthesis and clearing ROS.